Not beyond language: Wittgenstein and Lindbeck on the problem of speaking about God - Lim, Khay Tham Nehemiah (The University of Edinburgh, 2019)
The problem of speaking about God arises from the claim that God is utterly transcendent and is ‘wholly other’ from human or this-worldly existence. Another challenge is the profound sense of mystery that surrounds God’s being. In traditional theology, the response opted by some is to keep silent. This would seem to have been the position of the early Wittgenstein who famously declares, ‘What we cannot speak about we must pass over in silence.’ In this study, I take a different position by contending that it is still possible to speak about God—that he is not beyond language. My argument, however, is that although we may speak about God, our language cannot be pressed to yield precise definitions or complete explanations of the divine. So, while language about God can and does open up previously shrouded pathways leading us to know (more) about God, the sheer incommensurability between divine transcendence and its possible expression should leave us with ambiguities and gaps in our understanding. My argument is wedged between two extreme understandings of religious language. On the one hand, there is the tendency to regard religious statements as having no factual content, or at best, as expressing moral or ethical intentions to follow a certain way of life. The consequence of this is that speech about God is rendered empty or even inauthentic, giving rise to scepticism. In contrast to this approach, however, is the tendency to assume that words are perfectly fitted to give believers precise explanations and render God (or, indeed, reality as a whole) completely intelligible. The consequence of the latter tendency is absolutism or idolatry. In support of my case, I will explore the philosophy of Wittgenstein and appropriate his insights to shed light on the nature of language and its use. Many of his notions, such as ‘meaning-as-use’, ‘language-games’, ‘form(s)-of-life’, and the ‘private-language-argument’ will be discussed. What will be stressed is Wittgenstein’s overall view that language is not merely a system of signs for stating facts or making truth-claims—even about God—but that the speaking of language is grounded in the setting of everyday life. Meaning, in a large class of cases, is bound up with ‘use’: what a word or statement actually means depends on how it is used in relation to the conventions, practices and needs of a given community. I will also seek to learn from George Lindbeck, a theologian whose postliberal theology was inspired by Wittgenstein and who has sought to maintain a balance between two not dissimilar poles of conceiving the use of religious language, namely, the ‘cognitive-propositional’ and the ‘experiential-expressive’ theories of religion. The conception of language I am concerned to advance here, however, does not deny the possibility of truth, and it does not imply that ‘anything goes’. The question of truth will be included in the discussion. Other than attempting to navigate a via media between scepticism and absolutism, my approach can also veer us toward a better appreciation of the proper role of language in speaking about God, and to an understanding of religion that is much more than that of being fixated with inquiring into or explaining about ‘how things are in the world’, as though religion were a science.
Keywords: philosophy of language; Ludwig Wittgenstein; George Lindbeck; cognitive-propositional; cultural-linguistic; experiential-expressive; religious language